2020
DOI: 10.1002/ajhb.23533
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity levels among the adults of Majha region of Punjab, India: A cross‐sectional study

Abstract: Objectives: To construct a physical activity profile of the adult population of the Majha region of the Indian Punjab. Methods: The study included a total of 1130 adult participants aged 18 to 64 years comprising both genders, from rural, urban, and different sociodemographic backgrounds from the four districts of the Majha region of Punjab. The WHO's STEPwise approach to Surveillance instrument for noncommunicable diseases was used to collect data for the selected variables such as physical activity levels, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Similar results were also reported several other studies. [ 3 , 10 , 24 - 26 ] Similar to the present study Aslesh et al . [ 27 ] in their study revealed that there was no significant difference between the level of physical activity and age groups ( P = 0.900).…”
Section: Discussionsupporting
confidence: 91%
“…Similar results were also reported several other studies. [ 3 , 10 , 24 - 26 ] Similar to the present study Aslesh et al . [ 27 ] in their study revealed that there was no significant difference between the level of physical activity and age groups ( P = 0.900).…”
Section: Discussionsupporting
confidence: 91%
“…Similar findings were reported by previous studies. NCDs, such as cardiovascular and neurological diseases, were events that are strongly associated with physical inactivity, which produced catabolic effects on the muscles and nervous and cardiovascular systems, which in conjunction favor the physical performance decline [60][61][62][63]. Besides, decreased mobility from joint diseases was a limiting factor for adherence to PA in rural residents with NCDs [64].…”
Section: Ncdsmentioning
confidence: 99%
“…Similar findings were reported by previous studies. NCDs, such as cardiovascular and neurological diseases, were events that are strongly associated with physical inactivity, which produced catabolic effects on the muscles, nervous and cardiovascular systems, which in conjunction, favor the physical performance decline [58][59][60][61]. Besides, decreased mobility from joint diseases was a limiting factor for adherence to PA in rural residents with NCDs [62].…”
Section: Status Of Ncds Is An Influencing Factor Of Pamentioning
confidence: 99%